The effect of vaccination regimen on the transfer of foot and mouth disease antibodies from the sow to her piglets. - Francis, M. J. (Cambridge University Press, 1984)
Four groups of pregnant sows were inoculated with type O1 foot and mouth disease (FMD) oil emulsion vaccine at various times before farrowing and samples of the sow's serum, colostrum and milk, and piglet's serum, collected during the first week after farrowing, were analysed for FMD virus neutralizing activity. No FMD neutralizing antibodies were detectable in the piglets serum at birth but they were present 1.5 h after suckling and peak titres were reached 1-3 days later. There was no significant difference between the antibody titres of colostrum samples collected from different teats at farrowing. However, similar samples collected 3 days later showed significant (P less than 0.005) fore to hind variation. The principal FMD virus neutralizing antibody class present in the sow's serum at farrowing and in their 3-day-old piglets was governed by the inoculation schedule employed. When the last vaccinations were given congruent to 30 days before farrowing (dbf) the predominant FMD virus neutralizing class was IgG. However, when the sows were vaccinated only congruent to 12 dbf the predominant class was IgM. A significant correlation was observed between the sow's serum titres and colostrum titres at farrowing (r = 0.90), and also between sows colostrum titres at farrowing and their 3-day-old piglets serum titres (r = 0.99).